Experimental Study Of Desiccant Material Pressure Drop - Chuah, Siong Wei (Universiti Sains Malaysia, 2022)
Nowadays, energy demand is increasing due to the increase population and standard of living. Efficiency of the heating, ventilation and air-conditioning (HVAC) will consuming less energy and provide comfortable indoor environment. High humidity can cause malfunction in data server and spread of bacteria and virus. Desiccant materials in desiccant air conditioning can absorb large amount moisture from air and can be desorbed easily at low regeneration temperature. Three different types of desiccant materials such as desiccant clay, activated alumina, and silica gel are used as desiccant in this experiment. Different porosity of desiccant is produced due to different sizes of different desiccants. The desiccant porosity is the ratio of void volume per total volume. There are three different voltage supplied to the blower in this experiment which is 163.2V, 2176V and 272V. A new design desiccant wheel is proposed for the desiccant material pressure drop experiment. For three different voltage supplied to the blower in this experiment, when desiccant porosity decreased, the pressure drop increased slight. Maximum and minimum inlet velocity decrease slightly when the porosity of the desiccant decrease, for all the different voltage supplied to the blower. A pressure drop maintain in small amount of increase when across new design of desiccant wheel.